2013
DOI: 10.1098/rsif.2013.0174
|View full text |Cite
|
Sign up to set email alerts
|

Entrapment of bed bugs by leaf trichomes inspires microfabrication of biomimetic surfaces

Abstract: Resurgence in bed bug infestations and widespread pesticide resistance have greatly renewed interest in the development of more sustainable, environmentally friendly methods to manage bed bugs. Historically, in Eastern Europe, bed bugs were entrapped by leaves from bean plants, which were then destroyed; this purely physical entrapment was related to microscopic hooked hairs (trichomes) on the leaf surfaces. Using scanning electron microscopy and videography, we documented the capture mechanism: the physical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 33 publications
1
46
0
1
Order By: Relevance
“…Szyndler et al . [15] previously showed that the hooked trichomes in kidney bean ( Phaseolus vulgaris ) physically entrap and impale bedbugs ( Cimex lectularius ), thereby preventing them from moving on the leaf surface. We also observed physical damage to caterpillars (leakage of hemolymph) in our experiments, mainly caused by the sharp spikes of stellate trichomes.…”
Section: Discussionmentioning
confidence: 99%
“…Szyndler et al . [15] previously showed that the hooked trichomes in kidney bean ( Phaseolus vulgaris ) physically entrap and impale bedbugs ( Cimex lectularius ), thereby preventing them from moving on the leaf surface. We also observed physical damage to caterpillars (leakage of hemolymph) in our experiments, mainly caused by the sharp spikes of stellate trichomes.…”
Section: Discussionmentioning
confidence: 99%
“…The capture mechanism involved the physical impaling of bed bug feet (tarsi) by hooked trichomes, in a distinct way from the Velcro-like mechanism of non-piercing entanglement. Using bean leaves as templates, and plant cell wallslike polymers, Szyndler et al (2013) microfabricated surfaces indistinguishable in geometry from the real leaves, including the trichomes. Despite snagging the bed bugs temporarily they did not hamper their locomotion as effectively as natural bean leaves.…”
Section: Non-glandular or Glandular Structuresmentioning
confidence: 99%
“…Based on popular knowledge that strewn kidney beans (Phaseolus vulgaris) leaf were used for trapping bed bugs, Szyndler et al (2013) identified the structural features involved in the mechanical capture by these leaves, in order to design biomimetic surfaces for bed bug ⁄ ä (Figueiredo and Pais 1992), (h and n). (Figueiredo and Pais 1994).…”
Section: Non-glandular or Glandular Structuresmentioning
confidence: 99%
“…Based on popular knowledge that strewn kidney beans (Phaseolus vulgaris) leaf were used for trapping bed bugs, Szyndler et al (2013) identified the structural features involved in the mechanical capture by these leaves, in order to design biomimetic surfaces for bed bug ⁄ ä trapping. The capture mechanism involved the physical impaling of bed bug feet (tarsi) by hooked trichomes, in a distinct way from the Velcro-like mechanism of non-piercing entanglement.…”
Section: Non-glandular or Glandular Structuresmentioning
confidence: 99%